Chemoenzymatic synthesis and biological evaluation of 2- and 3-hydroxypyridine derivatives against Leishmania mexicana - Garcia Liñares, Guadalupe Eugenia (2012)
A series of hydroxyalkyl and acyloxyalkyl derivatives of 2- and 3-hydroxypyridine was synthesized and their biological activity was evaluated as growth inhibitors of protozoan Leishmania mexicana. Thirty novel compounds were obtained through a chemoenzymatic methodology in two reaction steps. The influence of various reaction parameters in the enzymatic step, such as enzyme source, acylating agent/substrate ratio, enzyme/substrate ratio, solvent and temperature, was studied. Some of the evaluated compounds showed a remarkable activity as Leishmania mexicana growth inhibitors, obtaining the best results with the acetylated derivatives. The advantages showed by the enzymatic methodology, such as mild reaction conditions and low environmental impact, make the biocatalysis a convenient way to prepare these derivatives of substituted pyridines with application as potential antiparasitic agents. © 2012 Elsevier Ltd. All rights reserved.